2017
DOI: 10.1016/j.mam.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Folate status and colorectal cancer risk: A 2016 update

Abstract: The consensus of epidemiologic evidence indicates that an abundant intake of foodstuffs rich in folate conveys protection against the development of colorectal cancer, and perhaps some other common cancers as well. Pre-clinical models substantiate that the relationship is a genuinely causal one. Pre-clinical models have also lent mechanistic insights into the biochemical and molecular pathways by which adequate folate exposure conveys these protective effects, and human studies are beginning to confirm the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 84 publications
(93 reference statements)
1
31
0
Order By: Relevance
“…Folate biosynthesis by the gut microbiota is a source of the water-soluble tetrahydrofolates which play an essential role in human metabolism 47. Inadequate status of folate has been implicated in increased risk of colon cancer especially if precancerous lesions exist 48. This may be applicable to gastric carcinogenesis, given our observation in this study.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Folate biosynthesis by the gut microbiota is a source of the water-soluble tetrahydrofolates which play an essential role in human metabolism 47. Inadequate status of folate has been implicated in increased risk of colon cancer especially if precancerous lesions exist 48. This may be applicable to gastric carcinogenesis, given our observation in this study.…”
Section: Discussionmentioning
confidence: 60%
“…This may be applicable to gastric carcinogenesis, given our observation in this study. Optimisation of bacterial production of folate may reduce the risk of IM development 48. Nucleotide oligomerisation domain containing proteins (NOD) are conserved pattern recognition receptors that are stimulated by pathogen-associated molecular patterns (PAMPS).…”
Section: Discussionmentioning
confidence: 99%
“…Folates are essential for various physiological and developmental functions in the human body (Saini et al, 2016). They are critical for the embryonic development (Kim et al, 2009) and inadequate intakes may result in higher risk of certain cancers (Mason and Tang, 2016). Therefore, since humans cannot synthesize this vitamin, its intake needs to be ensured from dietary sources.…”
Section: Vitaminsmentioning
confidence: 99%
“…Studying one‐carbon metabolites individually may give ambiguous results, due to the interdependence between the metabolites . We have previously used a machine learning‐based Bayesian network approach to simultaneously study >30 factors involved in one‐carbon metabolism in relation to CRC risk .…”
Section: Introductionmentioning
confidence: 99%
“…24,27,28 Studying one-carbon metabolites individually may give ambiguous results, due to the interdependence between the metabolites. 29 We have previously used a machine learningbased Bayesian network approach to simultaneously study >30 factors involved in one-carbon metabolism in relation to CRC risk. 18 The study confirmed the importance of folate, riboflavin and PLP relative to other metabolites involved in one-carbon metabolism.…”
Section: Introductionmentioning
confidence: 99%